2017
DOI: 10.5039/agraria.v12i1a5411
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects and predation behavior of Ceraeochrysa cubana against Spodoptera frugiperda

Abstract: Mortality of neonate larvae and eggs of Spodoptera frugiperda has an important contribution to the management of this pest. This work aimed to determine the development, quantify the consumption, the time of search and handling of eggs of S. frugiperda by Cereaochrysa cubana. The duration of development and the survival of C. cubana were determined using eggs of the alternative prey Anagasta kuehniella; eggs, newborn caterpillars and combined feeding of egg + newborn caterpillars of S. frugiperda. The daily an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…For Nunes et al (2017), the smaller prey size in relation to the predator and its fast movement may make the first instar larvae need more time to find the prey. Under field conditions, prey finding by the predator can be facilitated by infestation and gregarious aphid behavior in plants.…”
Section: Searching Time and Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…For Nunes et al (2017), the smaller prey size in relation to the predator and its fast movement may make the first instar larvae need more time to find the prey. Under field conditions, prey finding by the predator can be facilitated by infestation and gregarious aphid behavior in plants.…”
Section: Searching Time and Handlingmentioning
confidence: 99%
“…Handling time of H. foeniculi nymphs by C. cubana larvae did not present significantly difference between predator instars, as well as in relation to previous diets (Table 4). Nunes et al (2017), in a study on biological aspects and behavior of C. cubana predation on Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae), found that the mean time taken by the chrysopidae to attack and consume prey decreased according to its development.…”
Section: Searching Time and Handlingmentioning
confidence: 99%
“…Nunes et al . (2017) reported that the third-instar larvae of Ceraeochrysa cubana (Hagen) could consume 47.4 eggs and 63.5 newborn caterpillars of S. frugiperda daily, which is similar to consumption by C . formosa (46.2 ± 8.9 eggs and 66.8 ± 13.3 first-instar larvae) (Li et al ., 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Ceraeochrysa cubana is widespread in the Neotropics, has resistance to various insecticides (Cordeiro et al 2010;Ono et al 2017) and preys on several agricultural pests, such as Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) (Nunes et al 2017), Aleurocanthus woglumi Ashby, 1915 (Hemiptera: Aleyrodidae) (Oliveira et al 2016) and Aphis gossypii Glover, 1877 (Hemiptera: Aphididae) (Alcantra et al 2008). Our results suggest that C. cubana is well adapted to the climatic and environmental conditions in Acre, and may be a suitable candidate for use in biological control programs for coffee pests in Acre, such as Praelongorthezia praelonga (Douglas, 1891) (Hemiptera: Ortheziidae), Leucoptera coffeella (Guérin-Mèneville & Perrottet, 1842) (Lepidoptera: Lyonetiidae) and Brevipalpus phoenicis (Geijskes, 1939) (Acari: Tenuipalpidae), which are known to be predated by other Chrysopidae species (Chrysopa sp.…”
Section: Acta Amazonicamentioning
confidence: 99%